THE INFLUENCE OF DEVIANT FORMS OF DEVELOPMENT OF ENTREPRENEURIAL ENVIRONMENT ON THE ECONOMIC SECURITY OF UKRAINIAN ENTERPRISES (International Journal of Innovative Technologies in Economy, 2020)
The article reveals the role of permanent monitoring of the exogenous environment for deviant forms of business environment development in order to develop and adjust the mission, strategy, operational measures of anti-inflation and anti-crisis nature to ensure economic security of economic entities. For this purpose, the evolution and essence of corruption are considered, as this fact not only reflects the negative trends in society, but also hinders the full progressive economic and political development of the state. Also, the existence of corruption and the generation of huge corruption losses in the course of corrupt interaction of corrupt officials with entrepreneurs and citizens can lead not only to direct social losses, but also to distort the institutional foundations of society, which negatively affects the economic security of enterprises. The analysis of deviant forms of business environment development is carried out and it is established that corruption is the most significant problem for business development in Ukraine. The consequences of this problem have been identified, which include the shadowing of business, the prevalence of illegal schemes and means of influence, the despair of a large number of entrepreneurs, which threatens the public system with destruction and leveling of the domestic legal system.